The Perspective Matters! Multisensory Integration in Ego-Centric Reference Frames Determines Full-Body Ownership - Petkova, Valeria I.; Khoshnevis, Mehrnoush; Ehrsson, H. Henrik (Frontiers in Psychology, 2011)
Recent advances in experimental science have made it possible to investigate the perceptual processes involved in generating a sense of owning an entire body. This is achieved by full-body ownership illusions which make use of specific patterns of visual and somatic stimuli integration. Here we investigate the fundamental question of the reference frames used in the process of attributing an entire body to the self. We quantified the strength of the body-swap illusion in conditions where the participants were observing this artificial body from the perspective of the first or third person. Consistent results from subjective reports and physiological recordings show that the first person visual perspective is critical for the induction of this full-body ownership illusion. This demonstrates that the multisensory integration processes producing the sense of corporeal self operates in an ego-centric reference frame.